THE INFLUENCE OF FINTECH, SOCIAL MEDIA AND E-COMMERCE ON INCREASING UMKM INCOME IN BONTANG CITY, EAST KALIMANTAN - sulaiman, sulaiman; Rahim, Abd; Pratama, Aditya; Firmannudin, Firmannudin (Program Studi Manajemen Fakultas Ekonomi Universitas Palembang, 2025)
Abstract: MSMEs play a crucial role in Indonesia's economy, including in Bontang City, East Kalimantan. In the digital era, the use of financial technology (Fintech), social media, and e-commerce has the potential to increase MSME income. However, the effectiveness of each technology in supporting MSME growth remains unclear, necessitating further research. This study aims to analyze the impact of Fintech, social media, and e-commerce on the income growth of MSMEs in Bontang City and to identify the challenges faced in adopting digital technology. A quantitative research approach was used, employing a survey method with 393 MSME respondents in Bontang City. Multiple linear regression analysis was conducted to examine the relationship between Fintech, social media, e-commerce, and MSME income. The findings indicate that e-commerce has a positive and significant impact on MSME income growth. However, the use of Fintech and social media does not significantly contribute to increased MSME income. Although social media and Fintech are widely used by MSMEs, their effectiveness in boosting income remains limited. The primary barriers to digital technology adoption among MSMEs in Bontang City include low digital literacy, unequal access to technology, and a lack of understanding of effective digital marketing strategies. E-commerce has proven to be the most effective tool in increasing MSME income compared to Fintech and social media. Therefore, optimizing the use of Fintech and social media and improving digital literacy among MSME players are crucial. Government support in the form of training and digital infrastructure development is also necessary to accelerate MSME digital transformation in Bontang City.